DEVELOPMENT OF WAQF ANAK CUCU LAND IN LIMBONG KAPAL, ALOR STAR: A STUDY CASE - Hamid, Muhammad Hamizan Ab; Rani, Mohd Afandi Mat; Ramli, Rusydi; Feisal, Albert; Noor, Nor Adila Mohd; Haron, Nurfaradilla; Hakim, AM (CENTRAL ASIA AND THE CAUCASUS, 2022)
Waqf anak cucu is a transactional asset that is unique in Islam. It is not only view as a form of devotion to Allah but also a social responsibility to the community. Waqf anak cucu has a high socio economy value to develop the community. This paperwork will discuss on the development of waqf anak cucu in Kedah. This paperwork will also include inquiry about the development of waqf anak cucu and its potential development as well as the benefits. This research uses qualitative method, which are informational research to collect data on waqf and field work that involve interviews with important key people to get the actual and primary information from those who are directly involve with the development of waqf anak cucu. Waqf anak cucu is vital to providing a wider perspective of the process and characteristics of family waqf. This will help the public to better comprehend the family waqf in order to properly practice it. It can be inferred from concise review of related studies that the development and sustainability of family waqf depends on all its aspects and characteristics. The inclination of waqif to contribute (generosity) must be maintained; individuals serving the role of mutawalli should improve their management skills, insights of Islamic scholars must be taken into consideration, while the responsibility of Islamic leaders to provide full support must be maintained so that family waqf will constantly be able to significantly empower the Ummah. Research shows that waqf anak cucu has its specialty to ensure continuous benefits to the family. A good development of waqf anak cucu is crucial to make sure that the assets are developed and the benefits from it can continue to grow for the benefit of the community.